Experience in prenatal genetic testing and reproductive decision-making for monogenic disorders from a single tertiary care genetics clinic in a low-middle income country - Amna Hanif; Fizza Akbar; Salman Kirmani; Amyna Jaffarali; Ghulam Zainab; Ayesha Malik; Zeeshan Ansar; Bushra Afroze (BMC, 2023)
Abstract Objectives Explore health-care seeking behaviour among couples with pregnancies at-risk of monogenic disorders and compare time duration for obtaining Prenatal Genetic Test (PGT) results based on (i) amniocentesis and Chorionic Villus Sampling (CVS) (ii) in-house testing and out-sourced testing. Report the spectrum of monogenic disorders in our cohort. Methods Medical records of women consulting prenatal genetic counselling clinic at Aga Khan University Hospital, Karachi from December-2015 to March-2021 with history of miscarriage or a monogenic disorder in previous children were reviewed. Results Forty-three pregnancies in 40 couples were evaluated, 37(93%) were consanguineous. Twenty-five (63%) couples consulted before and 15(37%) after conception. Thirty-one (71%) pregnancies underwent CVS at the mean gestational age of 13-weeks and 6-days ± 1-week and 3-days and amniocentesis at 16-weeks and 2-days ± 1-week and 4-days. PGT for 30 (70%) pregnancies was outsourced. The mean number of days for in-house PGT was 16.92 ± 7.80 days whereas for outsourced was 25.45 ± 7.7 days. Mean duration from procedure to PGT result was 20.55 days after CVS compared to 28.75 days after amniocentesis. Eight (18%) fetuses were homozygous for disease-causing variant for whom couples opted for termination of pregnancy (TOP). Twenty-six monogenetic disorders were identified in 40 families. Conclusion Proactive health-care seeking behaviour and TOP acceptance is present amongst couples who have experienced a genetic disorder.